Synthesis, physicochemical characterization, and crystallization of a putative retro-coiled coil. - Liu, N. (Cold Spring Harbor Laboratory Press, 1998)
An artificial HIV enhancer-binding polypeptide has recently been dimerized by covalently linking it to the leucine zipper motif of the yeast transcriptional activator GCN4 (Liu N et al., 1997, Eur Biophys J 25:399-403). Although it seemed that the dimerization of this peptide could be best achieved by the use of the retro sequence of the leucine zipper, this approach was not implemented in the original construct. As the first step toward the synthesis of a basic region-retro leucine zipper HIV enhancer-binding fusion protein, we have now prepared the retro version of the leucine zipper (r-LZ35) and performed initial physicochemical characterization. Circular dichroism and sedimentation equilibrium studies showed that, at concentrations < 100 microM, the retro peptide was an unstructured monomer. At higher concentrations, however, the monomer was in equilibrium with a tetramer and, at 1 mM, the retro peptide was almost fully helical. N-terminal extension of the retro peptide by the tripeptide Cys-Gly-Gly resulted in a 38-residue polypeptide that could be covalently dimerized by forming a disulfide bond between two chains to give the peptide (r-LZ38)2. Even in the low micromolar concentration range peptide (r-LZ38)2 formed a stable, noncovalent, helical dimer as revealed by circular dichroism and sedimentation equilibrium in the presence and absence of guanidinium chloride. (r-LZ38)2 has been crystallized and X-ray structural analysis is under way. The disulfide-crosslinked retro-leucine zipper may lend itself to interesting protein structural studies, including protein design. The present work also highlights the structural and functional potential of retro proteins in general.